Tenascins in Retinal and Optic Nerve Neurodegeneration - Reinhard, Jacqueline; Roll, Lars; Faissner, Andreas (Frontiers in Integrative Neuroscience, 2017)
Tenascins represent key constituents of the extracellular matrix (ECM) with major impact on central nervous system (CNS) development. In this regard, several studies indicate that they play a crucial role in axonal growth and guidance, synaptogenesis but also boundary formation. These functions are not only important during development, but also for regeneration under several pathological conditions. Additionally, tenascin-C also represents a key modulator of the immune system and inflammatory processes. In the present review, we focus on the function of tenascin-C and tenascin-R in the diseased CNS, specifically after retinal and optic nerve damage and degeneration. We summarize the current view on both tenascins in diseases such as glaucoma, retinal ischemia, age-related macular degeneration or diabetic retinopathy. In this context, we discuss their expression profile, possible functional relevance, remodeling of the interacting matrisome and tenascin receptors, especially under pathological conditions.